DIGITALISASI PELAPORAN KEUANGAN PERSPEKTIF UMKM DI KOTA MATARAM - nungki kartikasari; Iman Waskito; Eni Indriani (Jurnal Riset Akuntansi, 2022)
This study aims to determine the perspective of MSMEs in Mataram City in responding to the digitization of financial reporting. The perception of MSMEs in Mataram City is the object of this research. The method used is descriptive analytical. The results showed that 75.74% of the 136 MSMEs in Mataram City recorded money transactions related to business, but less than 25% compiled their financial statements. The results of this study also show that 9.56% of MSMEs could store and access financial reports compiled online.